Histotripsy: the first noninvasive, non-ionizing, non-thermal ablation technique based on ultrasound. (1st January 2021) - Xu, Zhen; Hall, Timothy L.; Vlaisavljevich, Eli; Lee, Fred T.
Abstract: Histotripsy is the first noninvasive, non-ionizing, and non-thermal ablation technology guided by real-time imaging. Using focused ultrasound delivered from outside the body, histotripsy mechanically destroys tissue through cavitation, rendering the target into acellular debris. The material in the histotripsy ablation zone is absorbed by the body within 1–2 months, leaving a minimal remnant scar. Histotripsy has also been shown to stimulate an immune response and induce abscopal effects in animal models, which may have positive implications for future cancer treatment. Histotripsy has been investigated for a wide range of applications in preclinical studies, including the treatment of cancer, neurological diseases, and cardiovascular diseases. Three human clinical trials have been undertaken using histotripsy for the treatment of benign prostatic hyperplasia, liver cancer, and calcified valve stenosis. This review provides a comprehensive overview of histotripsy covering the origin, mechanism, bioeffects, parameters, instruments, and the latest results on preclinical and human studies.